In Silico Analysis of Osa-miR164 Gene Family in Rice (Oryza Sativa) - Tien, Vuong Quang; Duong, Nguyen Huy; Nhan, Dao Trong; Vu, Phan Minh; Phuc, Do Thi (VNU Journal of Science: Natural Sciences and Technology, 2021)
MicroRNA (miRNA) is a small non-coding RNA molecule containing about 22- 24 nucleotides, which functions in post-transcriptional regulation of gene expression. Previous reports have shown that miRNA plays an important role on the resistance ability of plants to adverse conditions. Rice ( Oryza sativa) is a major food crop. Climate change makes the situation of salinity and drought in Vietnam worse, significantly affects rice cultivation area, leading to the decrease of the quantity and the quality of rice grains. In this research, we focused on miR164 family in rice. By using bioinformatics approach, we analyzed sequences of all osa-miR164 belonging to rice miR164 family, evaluated the expression profile of osa-miR164 under different stress conditions, predicted cis-regulatory elements on osa-miR164 gene promoters, and simultaneously predicted miR164-targeted genes and their expressions. The results showed the high conserve in mature osa-miR164 sequences but not in the precursor sequences, different expression pattern of osa-miR164 gene members under stress conditions and various cis-regulatory elements present in osa-miR164 gene promoters which may explain for diverse expression pattern of osa-miR164 genes. Some potential target genes of osa-miR164 were identified and their expressions under different stress conditions were analyzed.